The United Nations Declaration on the Rights of Peasants and Other People Working in Rural Areas: One step forward in the promotion of human rights for the most vulnerable - Maria Natalia Pacheco Rodriguez; Luis Fernando Rosales Lozada (South Centre, 2020)
Peasants and other people living rural areas are among the most vulnerable in the world. In 2015, an estimated of 736 million people in the world lived in extreme poverty, of which 589 million – 80 per cent – live in rural areas. Despite increasing urbanization in the last decades, almost 45 per cent of the global population still lives in areas defined as rural, and most of them are among the poorest of the world. The situation is most likely worsening because of the COVID-19 pandemic. In 2018, the United Nations (UN) General Assembly, adopted the United Nations Declaration on the Rights of Peasants and Other People Working in Rural Areas by the supporting vote of a vast majority of countries. There are many reasons to consider the Declaration as one of the most relevant actions in the realm of human rights law taken by the United Nations in recent years. Some of them are the recognition of peasants as specific subjects of rights; the reaffirmation of existing standards tailored for the reality of people living in rural areas; and the development of international law to address existing gaps in the protection of their rights in complex subject matters such as the right to land, the right to seeds, and the right to means of production. In underscoring the importance of the Declaration for the world, this research paper narrates the process of construction of the Declaration, its contributions to international human rights law and stresses on its potential for poverty reduction and food security, in line with the sustainable development goals (SDGs) and the strategies of the UN Decade on Family Farming.
Keywords: 300; Civil and Political Rights; COVID-19; Food Security; Human Rights; Human Rights Council; International Law; La Via Campesina (LVC); Peasants; Poverty Reduction; Right to Food; Right to Health; Right to Land; Right to Means of Production; Right to Seeds; Right to Water; Sustainable Development Goals (SDGs); UN Decade on Family Farming; United Nations (UN); United Nations Declaration on the Rights of Peasants and Other People Working in Rural Areas; United Nations General Assembly (UNGA); Women's Rights